O banco óptico como ferramenta lúdica para o ensino de óptica geométrica - Lobo, Rodrigo Lins Mendes (2021)
Certainly, the biggest challenge faced by all physics teachers today and in the past is to make students have a sympathy for the contents of Physics. In this context, it is essential for the teacher to leave aside exclusively traditional classes with the blackboard and brush and reinvent himself, to show the student how beautiful the study of Physics is. For this to happen in a playful way, this work proposes to the teachers the use of a low cost optical bank to assist in the significant learning of the content of Geometric Optics to high school. This optical bench will serve as a support material for the teaching staff to be able to take some practice to the classroom, thus making the class more dynamic, interesting and with the participation of students in such a way, that they will raise questions about how and why that phenomenon is occurring. It was applied at the Ari de Sá Cavalcante, in Fortaleza – Ce, and the evolution of students after the application of the bank can be noticed, both in the understanding of the content and in the active participation of the Physics classes questioning the teacher, always in pursuit of meaningful learning. In the proposed optical bank, there are 6 experiments aimed at teaching the various contents of Geometric Optics, among which we can highlight: color of an object, dispersion of white light, principle of rectilinear propagation of light, luminous reflection, polarization and the study of spherical lenses.